17-2 EVALUASI PENGELOLAAN OBAT DAN PERBAIKAN BERDASARKAN DIAGRAM FISHBONE DI DINAS KESEHATAN KOTA X TAHUN 2024 - Yunartika Puspitasari; Jason Merari Peranginangin; Tri Wijayanti (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Effective and efficient drug management is a crucial component in supporting quality healthcare services, particularly at the local government level. This study aims to evaluate the performance of drug management at the Pharmacy Installation of the X City Health Office based on standard indicators, identify non-compliant indicators, and prioritize problems using the Hanlon method. This study uses a descriptive evaluative approach with data collection methods through a retrospective study of drug management documents from 2024, documentation and observation of data from 2025, and in-depth interviews with relevant parties. Data were analyzed based on national drug management indicator standards and content analysis. The priority scale of problems was determined using the Hanlon method. The evaluation results showed that of the 30 indicators analyzed, 60% did not meet standards. The highest priority problem was the non-compliance of drug items with the National Formulary (FORNAS), which had a systemic impact on other indicators. The main causes of the problem include limited human resources (HR) and training on FORNAS, the absence of standardized FORNAS selection and validation at the city level, mismatch between budget allocation and needs, a suboptimal information system, pressure from prescribers to procure non-FORNAS drugs, and the absence of a regular monitoring and evaluation system. The follow-up actions formulated include proposals for additional HR, technical training, improved cross-sector coordination, development of existing application systems, budget optimization, and implementation of regular monitoring and evaluation.